Theory of type-II superconductivity in ferromagnetic metals with triplet pairing - Mineev, V.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
The superconducting state in uranium compounds UGe2, URhGe and UCoGe is formed at temperatures far below the Curie temperature pointing on nonconventional nature of superconductivity in these materials — namely the superconductivity with triplet pairing. The emergence of superconductivity is accompanied by the slight magnetization expulsion typical for the type-II superconductors. Following classic Abrikosov paper I develop the theory of type-II superconductivity in application to two-band ferromagnetic metal with equal spin triplet pairing.